2021
DOI: 10.1186/s13075-021-02614-8
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of oral mucosal lesions and related factors in systemic lupus erythematosus patients

Abstract: Background Systemic lupus erythematosus (SLE) is a chronic inflammatory multi systematic disease of unknown aetiology. SLE has a wide range of symptoms. The most common symptoms are joint pain, skin rash and fever. Oral lesions in SLE manifest in a variety of forms, such as oral mucosal ulceration, mouth burns, xerostomia and salivary gland diseases, temporomandibular joint disease, periodontal disease, dysgeusia, white lesions, oedema, bleeding and petechiae. Obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 26 publications
0
16
0
8
Order By: Relevance
“…Numerous epidemiologic studies revealed that exposure to cigarette smoke is associated with increased risk of SLE ( Figure 2 ) ( 108 115 ). Furthermore, strong and consistent evidence suggests that current smoking is more risky than previous smoking ( 116 122 ).…”
Section: Effects Of Cigarette Smoking and Consumption Of Alcohol And ...mentioning
confidence: 99%
“…Numerous epidemiologic studies revealed that exposure to cigarette smoke is associated with increased risk of SLE ( Figure 2 ) ( 108 115 ). Furthermore, strong and consistent evidence suggests that current smoking is more risky than previous smoking ( 116 122 ).…”
Section: Effects Of Cigarette Smoking and Consumption Of Alcohol And ...mentioning
confidence: 99%
“…Similar findings were observed in a study conducted in Brazil which showed 58% of the patients reported with xerostomia due to immune attack on salivary glandular parenchyma. 17 Gingivitis was observed in 59% of patients while glossitis and mucositis were observed in 43% and 42% of patients respectively. 17% of patients who were using cyclosporine reported gingival hyperplasia.…”
Section: Discussionmentioning
confidence: 97%
“…The oral mucosa is the most affected one, in 8% to 45% of cases, mainly occurring in the buccal, palatine, and labial mucosa, as enanthematous or purpuric plaques, vesiculobullous lesions, erosions, and ulcers. 20 Nasal ulcerations are less common and other mucous membranes are rarely affected.…”
Section: Clinical Presentation and Differential Diagnosismentioning
confidence: 99%